Predictors of implementation in the Faith, Activity, and Nutrition dissemination and implementation study: application of the Consolidated Framework for Implementation Research (CFIR) in a statewide initiative. Issue 2 (28th March 2020) - Wilcox, Sara; Jake-Schoffman, Danielle E; Saunders, Ruth P; Kinnard, Deborah; Kaczynski, Andrew T; Hutto, Brent; James, Katherine L
Abstract : Churches reported large increases in providing opportunities, policies, messages, and pastor support for physical activity and healthy eating, and multiple organizational factors predicted these increases. Abstract: Faith-based organizations, with broad reach and trust, are well-positioned to promote health. The purpose of the study was to examine 12-month implementation and its predictors in the statewide Faith, Activity, and Nutrition (FAN) dissemination and implementation (D&I) study. Churches ( n = 93; 42% predominantly African American) in the [South Carolina] Conference of the United Methodist Church trained by Community Health Advisors participated in the study. Church FAN coordinators ( n = 92) completed implementation surveys regarding opportunities, policies, messages, and pastor support for physical activity (PA) and healthy eating (HE) at baseline and 12 months. FAN coordinators and pastors ( n = 93) completed CFIR-based measures at baseline, immediate post-training, and 12 months. Repeated measures ANOVAs tested change in PA and HE implementation composite scores; Cohen's d indicated magnitude of change. Mixed model linear regression tested whether CFIR items predicted 12-month implementation, controlling for baseline implementation. PA ( d = 1.42) and HE ( d = 2.05) implementation increased significantly over time. PA and HE implementation were significantly greater in predominantly African American (versus White) congregations, and HE implementation was greater in churches with <500 members. FAN coordinators' ratings of the inner setting (networks/communication, culture, tension for change, organizational rewards, readiness, and congregant needs) and implementation process (engaging opinion leaders and champions) domains were most predictive of implementation outcomes. Few pastor ratings related to implementation outcomes. This study identified constructs, guided by CFIR, that may be important for understanding PA and HE implementation in churches. Future studies will need to test them for replication. Greater changes in implementation outcomes among African American churches underscores the potential of promoting health equity through this setting.